When visual cues influence taste/flavour perception: a systematic review - Motoki, K; Spence, C; Velasco, C (Elsevier, 2023)
There has been a noticeable increase of interest in research on multisensory flavour perception in recent years. Humans are visually dominant creatures and a growing body of research has investigated how visual cues influence taste/flavour perception. At the same time, however, several null or limited findings have also been published recently; that is, studies showing either partial demonstrations or else failing to find any evidence in their data for the influence of specific visual cues on taste/flavour perception. By performing a systematic review and a critical evaluation of the literature that has been published to date, the present paper reveals whether and when visual cues (e.g., colour and shape) affect taste/flavour perception: The reviewed research demonstrates that visual cues can significantly affect taste/flavour perception under certain conditions, but that mixed, limited, and/or null results have also been reported in a number of other studies. We discuss potential moderators (the salience/attentional capture of visual cues, the strength of association between visual cues and taste/flavour, the perceived diagnosticity of visual cues regarding the signalling of taste/flavour, the evaluative malleability of food judgments) that might help to explain a number of the inconsistent findings that have appeared in the literature since 2011. Several important areas of future research in this area of inquiry are also identified.